World Food Supply A Global Development Studies Case Study. Revised Edition, 1975 - Spivey, J. Carlisle; Management Inst. for National Development, New York, NY. ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1975)
Designed for use in a secondary or undergraduate level course non global development, this case study examines the current crisis in the world food supply. The study is divided into three main parts, each dealing with a key question of world food supply: (1) What Is Hunger? (2) Why Is There Hunger? (3) What Is Being Done? Section 1 defines hunger in terms of nutrition, humanity, and development, providing a brief history of the food shortage. Section 2 analyzes the factors responsible for the present condition of the world food supply including the role of nature, the role of agricultural production, and the role of government policy. Section 3 discusses research and relief programs and the United Nations World Food Conference. Also included in the study is an instruction guide which suggests techniques and resources giving greater depth of understanding to the issues. The guide contains a discussion of key teaching strategies, tips on methodology, suggestions on topics and questions for classroom discussion, and information on resource materials and organizations. (Author/DE)
Educational level discussed: Higher Education.
Educational level discussed: Secondary Education.
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Developing Nations; Food; Futures (of Society); Global Approach; Higher Education; Hunger; Instructional Materials; Nutrition; Poverty; Resource Materials; Secondary Education; Social Studies; Teaching Methods; Units of Study; World Affairs; World Problems; Interdependence; Guides, General